Rh(iii)-Catalyzed sequential ortho-C–H oxidative arylation/cyclization of sulfoxonium ylides with quinones toward 2-hydroxy-dibenzo[b, d]pyran-6-ones. Issue 49 (15th May 2020) - Dong, Yaqun; Yu, Jin-Tao; Sun, Song; Cheng, Jiang
Abstract : A rhodium(iii )-catalyzed ortho -C–H functionalization of sulfoxonium ylides followed by intramolecular annulation reactions with quinones was described, where the carbonyl in sulfoxonium ylides served as a chelation group. Abstract : A rhodium(iii )-catalyzed ortho -C–H functionalization of sulfoxonium ylides followed by intramolecular annulation reactions with quinones was described, where the carbonyl in sulfoxonium ylides served as a chelation group. This protocol leads to the efficient formation of 2-hydroxy-6 H -benzo[ c ]chromen-6-one derivatives, proceeding with the cleavage of the C(O)–S bond in sulfoxonium ylides. This protocol featured high chemo-selectivity and functional group tolerance, where sulfoxonium ylides acted as the aroyl sources.